A phase I/II study of leucovorin, carboplatin and 5-fluorouracil (LCF) in patients with carcinoma of unknown primary site or advanced oesophagogastric/pancreatic adenocarcinomas. - Rigg, A. (Nature Publishing Group, 1997)
Carcinoma of unknown primary site (CUPS) accounts for 5-10% of all malignancies. Forty patients with metastatic CUPS or advanced oesophagogastric/pancreatic adenocarcinomas were recruited. Eligibility included ECOG performance status 0-2, minimum life expectancy of 3 months and measurable disease. The regimen consisted of bolus intravenous 5 fluorouracil (5-FU) and leucovorin (20 mg m-2) days 1-5 and carboplatin (AUC5) on day 3. The leucovorin/carboplatin/5-FU (LCF) was repeated every 4 weeks. The starting dose of 5-FU was 350 mg m-2 day-1 with escalation to 370 and then 400 mg m-2 day -1 after the toxicity at the previous level had been assessed. The maximum tolerated dose (MTD) was defined as the dosage of 5-FU that achieved 60% grade 3/4 toxicity. In addition, objective and symptomatic responses, quality of life and survival were assessed. The MTD of 5-FU in the LCF regimen was 370 mg m-2. The predominant toxicity was asymptomatic marrow toxicity. The 350 mg m-2 level was then expanded. There were two toxic deaths due to neutropenic sepsis, one at 370 mg m-2 after one course and one at 350 mg m-2 after four courses. The objective response rate was 25% with one complete response (CR) and nine partial responses (PRs). The median duration of response was 3.4 months (range 1-10). The CR and eight of the nine PRs were in CUPS patients. Twelve patients developed progressive disease on LCF. Median survival for all 40 patients was 7.8 months (10 months median survival for those treated at 350 mg m-2). The majority of patients described a symptomatic improvement with LCF chemotherapy. The recommended dose of 5-FU for future studies is 350 mg m-2 combined with leucovorin 20 mg m-2 and carboplatin (AUC5).